2021
DOI: 10.1007/s40735-021-00472-0
|View full text |Cite|
|
Sign up to set email alerts
|

Rain Erosion Maps for Wind Turbines Based on Geographical Locations: A Case Study in Ireland and Britain

Abstract: Erosion rates of wind turbine blades are not constant, and they depend on many external factors including meteorological differences relating to global weather patterns. In order to track the degradation of the turbine blades, it is important to analyse the distribution and change in weather conditions across the country. This case study addresses rainfall in Western Europe using the UK and Ireland data to create a relationship between the erosion rate of wind turbine blades and rainfall for both countries. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…As noted by Rasool et al [27], data from RET experiments show enhanced degradation in both the presence of saline and acidic solutions. Pugh et al [25,26] supports this, noting that the presence of salt within the working fluid appears to enhance rain erosion through the crystallisation of salts on the surface. The data presented by Law and Koutsos [12] support this with wind parks closer to the coast displaying more severe damage in a shorter period than those in remote regions.…”
Section: Compositionmentioning
confidence: 93%
See 1 more Smart Citation
“…As noted by Rasool et al [27], data from RET experiments show enhanced degradation in both the presence of saline and acidic solutions. Pugh et al [25,26] supports this, noting that the presence of salt within the working fluid appears to enhance rain erosion through the crystallisation of salts on the surface. The data presented by Law and Koutsos [12] support this with wind parks closer to the coast displaying more severe damage in a shorter period than those in remote regions.…”
Section: Compositionmentioning
confidence: 93%
“…Salt concentrations are typically much higher than acidic pollutants and are of interest in situations where materials (including polymers) are prone to corrosion [15,16,24]. Recent evidence [12,[25][26][27] suggests enhanced degradation due to the presence of sea salt, acidity or at sites in close proximity to quarries. The influence of salt will be more pronounced at sites near the coast or offshore.…”
Section: Introductionmentioning
confidence: 99%
“…The spatio-temporal analysis is accompanied by estimates of wind turbine blade mass loss monthly rates for a few selected cases by using experimental data from [9]. A table from an experiment performed in this reference [9] that links rain amounts in millimeters to blade mass loss in percentage is used in this work to provide insight into possible blade mass loss monthly rates for the period of interest. Methods in data processing in this work include linear interpolation to align data spatial resolution, as well as standard averaging procedures and classical computations of correlation matrices.…”
Section: Introductionmentioning
confidence: 99%
“…The meteorological data are used to predict erosion behavior based on the Springer model. It has been shown that offshore locations have more severe rain conditions than inland locations in several areas, such as Denmark [ 20 , 21 ], the British Isles [ 22 , 23 , 24 ] and Netherlands [ 25 ]. In the USA, inland conditions vary heavily, as measured by a radar [ 26 ], yet they have a significant effect on leading edge lifetime.…”
Section: Introductionmentioning
confidence: 99%